THE EVOLUTIONARY TRAJECTORY OF ORATORY: FROM ORAL TRADITION TO DIGITAL MASTERY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Oratory is not merely the act of public speaking; it is a fundamental communicative  practice that has evolved as a mirror to human civilization. It represents the intersection  of linguistic precision, psychological persuasion, and social governance.